Pulpal anesthesia in pediatric patients following supplemental mandibular buccal infiltration in vital permanent mandibular molars with deep caries - Papimon Chompu-inwai (2019)
© 2019, Springer-Verlag GmbH Germany, part of Springer Nature. Objectives: Inferior alveolar nerve block (IANB) does not always provide adequate pulpal anesthesia, and supplemental techniques have been investigated in adults. This study aimed to pre- and intraoperatively evaluate the success of pulpal anesthesia following supplemental mandibular buccal infiltration (SMBI) after failure of IANB in permanent mandibular molars with deep caries of pediatric patients. Materials and methods: Following IANB, preoperative pulpal anesthesia was assessed using the cold test, and success was defined when there was a negative response. In cases with failed IANB, SMBI was administered, and pulpal anesthesia was re-evaluated. A maximum of three SMBIs was allowed. After achieving successful preoperative pulpal anesthesia, treatment was then initiated. Intraoperatively, success of pulpal anesthesia was determined when the Wong-Baker FACES Pain Rating Scale reported by the patients was ≤ four. Results: Sixty molars of patients aged 9.6 ± 2.3 years were included in the study. The success of preoperative pulpal anesthesia following IANB was 33.3%. The overall cumulative preoperative pulpal anesthesia after three SMBIs was 95%. However, the success of intraoperative pulpal anesthesia was only 66.7%. Conclusions: SMBI greatly improved the success of preoperative pulpal anesthesia after failure of IANB. However, the success of preoperative pulpal anesthesia, confirmed by the cold test, does not always guarantee intraoperative pulpal anesthesia, especially in teeth with irreversible pulpitis. Clinical relevance: IANB produced low pulpal anesthesia in vital permanent mandibular molars with deep caries of pediatric patients. Clinicians should always prepare for supplemental injection both pre- and intra-operatively.